Antimicrobial activities and metabolites profiling of Heliotropium bacciferum Forssk. methanolic extract - Ahmed ABDELKHALEK; Moustafa ELSHAER; Abdulaziz AL-ASKAR; Przemysław KOWALCZEWSKI; Said BEHIRY (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2024)
In the present study, Heliotropium bacciferum Forssk. methanolic extract was tested for its antibacterial activities against Pectobacterium carotovorum, P. atrosepticum, Ralstonia solanacearum, and Streptomyces scabiei bacterial strains. The plant extract was also tested for its antifungal properties against strains of Fusarium oxysporum, Botrytis cinerea, and Rhizoctonia solani. The potent antibacterial activities were recorded against R. solanacearum after treatment with the extract at a concentration of 1000 µg/mL with an inhibition zone of 9.67 ±0.57 mm. The methanolic extract also showed promising antifungal effects against B. cinerea and F. oxysporum, with fungal growth inhibition percentages of 86.22 ±0.33% and 82.00 ±0.55%, respectively, which were higher than the standard antifungal drug. The plant extract’s HPLC analysis identified 12 phenolic compounds and 6 flavonoid compounds, with HPLC peaks matching the used standards. Gallic acid, chlorogenic acid, coffeic acid, ellagic acid, coumaric acid, syringic acid, methyl gallate, ferulic acid, vanillin, pyrocatechol, and cinnamic acid were the phenolic compounds that were identified. The flavonoid compounds found in the extracts were daidzein, naringenin, quercetin, kaempferol, hesperetin, apigenin, and rutin, arranged from high to low abundance. Furthermore, according to the GC-MS analysis, the most abundant compounds detected in the plant extract were n-hexadecanoic acid, 9,12-octadecadienoic acid (z,z), á-sitosterol, betulin, phorbol, cis-13-octadecenoic acid, and octadecanoic acid. These compounds in HPLC and GC-MS analyses were proven to have antibacterial as well as antifungal properties. Based on the obtained antimicrobial results, H. bacciferum methanolic extracts could be recommended as a promising antibacterial and antifungal agent, as well as a safe alternative to many antimicrobial pesticides for the environment and human health.